EFEKTIVITAS PEMBELAJARAN DARING SISWA KELAS X IPA TERHADAP HASIL BELAJAR BIOLOGI PADA KONSEP BIODIVERSITAS - Nadia; Yatin Mulyono (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2025)
This study aims to determine the effectiveness of online learning on students' learning outcomes in Class X IPA regarding biodiversity material in the biology subject. This research is based on the shift from face-to-face to online learning due to technological developments and the pandemic, which has encouraged the adoption of new learning methods. This study employed a quantitative, pseudo-experimental research method. The sample consisted of students in a tenth-grade science class at one of the state high schools. The students were divided into two groups: an experimental group that received online instruction and a control group that received face-to-face instruction. The instrument used was a validated, multiple-choice learning outcome test. Data analysis revealed a significant difference in learning outcomes between students who received online instruction and those who received face-to-face instruction. The average learning outcomes of students in the online group were sufficient, though lower than those in the face-to-face group. These results indicate that online learning is still limited in its effectiveness, particularly for materials requiring conceptual understanding, such as biodiversity. Therefore, it is necessary to develop online learning strategies that are more interactive and encourage active student involvement.